THE EFFECTIVENESS OF COGNITIVE BEHAVIORAL THERAPY TO REDUCE TUBERCULOSIS SELF-STIGMA: A LITERATURE REVIEW - Rezky Mulyana (Universitas Pelita Harapan, 2019)
Tuberculosis is an infectious disease with severe stigma. It is estimated that half of TBC patients have experienced internalization of stigma due to negative stereotypes from their community. The purpose of this review article review was to determine and to assess the effectiveness of cognitive behavioral therapy in reducing tuberculosis self-stigma. PRISMA flow diagram was used to show papers reviewed. Database used consisted of ProQuest, Science Direct, PubMed, Research Gate, Springer Link, and Google Scholar using keywords: CBT, AND Self Stigma, Cognitive behavioral therapy to reduce self stigma, CBT OR Self Stigma, Self-stigma AND CBT Intervention. articles published in English m 2003 to 2018 discussing HIV-related stigma and discrimination on patients with TB. Out of 15245 articles retrieved, 6% (4 articles) were reviewed. This review article using Downs and Black scale apprised the quality of the selected articles. Analysis method used thematic analysis and found stigma intervention as a theme. The results found four studies about the effectiveness of cognitive behavioral study and one study comparing cognitive behavioral therapy with psychoeducational (PE) found to be more helpful than CBT intervention. In another article showed more than a half of the sample (50%) from studies indicated that cognitive behavioral therapy can reduce self-stigma. Using cognitive behavioral therapy is effective for helping TBC patients to change negative beliefs and reframe their beliefs about their illness and the effect can help to reduce self-stigma.